U-shaped association between plasma cobalt levels and type 2 diabetes. (March 2021) - Cao, Benfeng; Fang, Can; Peng, Xiaolin; Li, Xiaoqin; Hu, Xueting; Xiang, Pan; Zhou, Li; Liu, Hongjie; Huang, Yue; Zhang, Qin; Lin, Shan; Wang, Mengke; et al.
Abstract: Aims: We aimed to investigate the association of plasma cobalt with newly diagnosed type 2 diabetes (T2D) and further explore the potential interaction effects between cobalt and several redox metals, such as manganese, copper and selenium. Design: A large case-control study including 4564 subjects was conducted. 2282 cases with newly diagnosed T2D and 2282 controls were matched by sex and age. The concentrations of cobalt and other metals in plasma were detected with inductively coupled plasma mass spectrometry (ICPMS). Results: The medians of the cobalt concentrations in plasma were 1.68 μg/dL for controls and T2D. There was a U-shaped relation between T2D and plasma cobalt, which was categorized into quartiles. After multivariable adjusted for the confounding factors, the odds ratios (ORs) of T2D across quartiles were 1.22 (95% CI: 1.01, 1.46), 1.12 (95% CI: 0.94, 1.35), 1.00 (reference) and 1.46 (95% CI: 1.22, 1.75), respectively. The association was almost consistent in subgroup analyses. According to the restricted cubic spline analysis, the lowest ORs of T2D was observed at the plasma cobalt of 2.00 μg/dL. There was a significant interaction between plasma cobalt and copper ( P  < 0.01). The ORs of T2D in those with medium concentration of plasma cobalt and copper was the lowest. Conclusions: Higher or lower concentrations of plasma cobalt were related to higher ORs of T2D. The inter-relationship among redox metals in T2D should be further investigated. Highlights: A U-shaped association was observed between plasma cobalt and T2D. There might exist potential inter-metal effects due to co-exposure of cobalt and copper in influencing the T2D risk.